Laparoscopic versus Open appendectomy in Acute Appendicitis - Batajoo, H; Hazra, N K (Journal of Nepal Health Research Council, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Although laparoscopic appendectomy is widely practiced nowadays, controversy still continues about the advantages of laparoscopic versus open appendectomy. To compare LA with OA to determine the length of hospital stay, post operative morbidity and length of operation. Methods: A retrospective study carried out, between February 2009 and January 2012, involving 226 patients (111 males and 115 females) with a diagnosis of suspected acute appendicitis. LA group consisted of 54 patients and OA group of 172 patients. The groups were compared by using Chi-square test for categorical variables and student t-test for continuous variables. Results: The mean length of hospital stay in LA was 2.69 days and in OA 4.03days (p<0.001). The mean operative time in LA was 61.52 minutes and in OA 39.61 minutes (p<0.001). Post operative wound infection was seen in one patient (1.8%) in LA group and 17 patients (9.8%) in OA group. Conversion to open surgery was not necessary. Conclusions: Laparoscopic appendectomy is as safe and effective as open procedure with major benefits like less post operative pain, decreased wound infection, less hospital stay and early return to normal activities. <span style="font-size: 11.0pt; line-height: 115%; font-family: ";Calibri";,";sans-serif";; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Keywords: acute appendicitis; laparoscopic appendectomy; open appendectomy<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>